ANALISIS KEMAMPUAN ANAK DALAM MENYUSUN KALIMAT BERDASARKAN MEDIA GAMBAR - Ema Khofifah; Dewi Siti Farida; Sary Sukawati (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study aims to describe the learning ability of children in composing sentences based on the media images at the age of 5-6 years. Given the importance of preparing children for continuing education to the next level, then this research is done so that children more easily follow the learning. When children are able to follow the learning process, then when learning children will feel comfortable and happy. In addition, composing the sentence is one of the indicators that must be achieved when entering the Early Childhood Education. Qualitative descriptive method is used because the research we do in accordance with the facts contained in the field. The total population of class B is twenty children, the sample of which is 10 children. As for the benchmarks in this study is the ability of children in mastering the amount of vocabulary, the ability in the mastery of sentence functions, and the ability of children in combining elements of sentence or so-called cohesion and coherence. There are several factors that can affect the ability of children in talking or composing sentences, namely the age factor of children, family environment, and physical factors.